Pesticide Residues in Coastal Tropical Ecosystems: Distribution, Fate and Effects - Taylor, Milton (CRC Press, 2009)
The coastal tropics comprise some of the most sensitive and yet the most understudied ecosystems in the world. Coastal plains and river valleys are also home to agriculture on a vast scale, and it is not surprising to find that streams and rivers receive the majority of agricultural runoff, carrying the residues of insecticides, fungicides and other pesticides into estuaries and coastal zones. There is a growing awareness of the urgent need to develop strategies to help productive, healthy and economically viable agriculture to coexist with natural resources. Pesticide Residues in Tropical Coastal Ecosystems brings together toxicology experts from around the world to assess pesticide burdens in many of the major food-producing tropical countries. It provides a unique set of case studies, chronicling pesticide usage and its ecotoxicological impact in coastal regions. A practical guide to recent research findings and applications, it is essential reading for environmental professionals, ecotoxicologists, marine chemists and agrochemists.